PENGARUH ISLAMISASI DALAM MEMBANGUN GAYA HIDUP SISWA SEKOLAH MENUJU GENERASI MUDA YANG MAJU - Harningsih Fitri Situmorang (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Islamization in the context of education is a systematic process aimed at instilling Islamic values into all aspects of students' lives. This study aims to analyze the influence of Islamization on the formation of students' lifestyle in order to create a young generation that is of good character, competitive, and morally upright. The approach used is a qualitative approach with a library research method, namely by reviewing various relevant literature on the concept of Islamization, character education, and the formation of an Islamic lifestyle in the school environment. The results of the study show that Islamization plays an important role in shaping students' personality and behavior through the integration of Islamic values in the curriculum, habituation of worship practices, and teachers' role modeling. Values such as honesty, responsibility, discipline, hard work, and social awareness become the foundation for the formation of an Islamic lifestyle that is able to balance spiritual, intellectual, and social aspects. In addition, Islamization contributes to strengthening students' moral resilience amid the currents of globalization and modernization that often carry materialistic and secular values. With the consistent implementation of Islamization, schools can become centers for shaping a young generation that is faithful, knowledgeable, ethical, and broad-minded. This generation is expected to be able to adapt to the times without losing their Islamic identity, and to become agents of change who bring progress to the nation and the ummah.